(untitled) (Communication & Society, 2018)
This paper analyses how the four candidates for prime minister in the 2016 Spanish general elections interacted with journalists and media professionals via Twitter, a social media platform considered by various experts (Bakshy et al., 2011) to be a “natural laboratory” for the study of patterns of information dissemination. NodeXL software, a well known open source social network analysis tool (Hansen et al., 2010), was used to capture activity corresponding to Twitter accounts maintained by these candidates and to identify the protagonists of online dialogues maintained during the election campaign as well as the characteristics and content of the messages they exchanged. Semantic relationships in the text and hashtags present in tweets were examined carefully in order to identify patterns of meaning. Findings indicate that the four politicians in question made a minimal effort to interact with journalists and media professionals via Twitter during the run-up to the 2016 elections. Analysis reveals that all used their Twitter accounts as an additional means of promoting their candidacies and publicizing party-related activities rather than a forum for discussing issues in depth. None appeared to be willing to enter into debates with journalists or the media through this particular social networking platform.